Response and remission after first line corticosteroid therapy in primary ITP - Mapimhidze, Danai (Adolescent Health Research Institute, 2026)
Background: Primary immune thrombocytopenia (ITP) is an acquired autoimmune disease characterized by an isolated thrombocytopenia of <100 x 109/L in the absence of identifiable secondary causes. Treatment is indicated when the platelet count is <20-30 x 109/L but may be commenced at higher platelet counts when the risk of bleeding is high. Corticosteroids are the backbone of initial treatment of ITP. There is a paucity of data in South Africa on the outcomes of newly diagnosed ITP patients treated with corticosteroids. Objectives: To describe the response, remission and clinical outcomes of newly diagnosed primary ITP patients on first-line corticosteroids. Methods: This was a retrospective cohort study of 68 patients with a new diagnosis of ITP, seen at the Clinical Haematology unit at Groote Schuur Hospital, over a 5-year period (20162020). Demographic and clinical data were obtained from paper and electronic record systems. All participants with secondary causes were excluded. The initial platelet responses to corticosteroids and the final outcomes at last follow up were determined. Initial platelet responses were classified into no response (NR), partial response (PR) and complete response (CR) in accordance with consensus definitions. Remission was defined as maintenance of a CR after being off corticosteroids for at least 6 months. Variables were described by frequencies and percentages or medians and interquartile ranges, as appropriate. Results: The majority of patients were females (88.2%) and the median age at diagnosis was 36 years (IQR 23.0-55.5). Most patients responded to corticosteroids (92.4%) with 74.2% achieving a CR and 18.2% achieving a PR. Only 5 patients failed to respond (7.6%). The median time to achieve CR was 15 (IQR: 8-25) days and the median time to achieve PR was 10.5 days (IQR 8-22). Half of the patients went into remission. Following remission, two patients (6.1%) subsequently relapsed at day 344 and day 777, respectively. Hypertension and/or diabetes were newly diagnosed in 10.6 % of patients. Conclusion: Corticosteroids are effective first line therapy for ITP but are not remission inducing in all patients. For those patients progressing to chronic ITP, there is a need to investigate cost effective treatment. Some patients are at high risk of developing new hypertension and diabetes mellitus on corticosteroids and should be monitored.